المحتوى الطحلبي ونوعية المياه الجوفية لبئرين من أبار الرحبة / جنوب بحر النجف / العراق - M. Alkam, Fo’ad; Kadhim Alasady, Raid; Abdul Wahid AlGhanmi, Haider (University of Thi-Qar Journal of Science, 2009)
The present study was conducted about some physical-chemical proprieties and algal composition in two artesian wells in Al-Rehba region south of Bahr Alnajaf from Novmber-2007 to April-2008. The results showed that water quality of the studied Artesian walls tend to be slightly alkaline, hard, and has overcritical Oxygen. Statistical analysis doesn’t show any significance differece between physical-Chemical proprieties of studies wells except in electrical conductivity(E.C) in April 2008.About36 Algal taxa has been classified in this study. Diatom(Bacillariophyceae) was the most dominant Algae (86.1%) followed by Blue green (Cyanophyceae) (13.9 %).